2016
DOI: 10.1186/s12889-016-2979-z
|View full text |Cite
|
Sign up to set email alerts
|

Access to mass media messages, and use of family planning in Nigeria: a spatio-demographic analysis from the 2013 DHS

Abstract: BackgroundNigeria has the highest population in sub-Saharan Africa with high birth and growth rates. There is therefore need for family planning to regulate and stabilize this population. This study examined the relationship between access to mass media messages on family planning and use of family planning in Nigeria. It also investigated the impacts of spatio-demographic variables on the relationship between access to mass media messages and use of family planning.MethodsData from the 2013 demographic and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
91
3
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(120 citation statements)
references
References 33 publications
23
91
3
3
Order By: Relevance
“…This study revealed that men who were exposed to the mass media had a lower likelihood to want more children than men without media exposure. This was also observed by Gupta et al (2003), Ajaero et al (2016).…”
Section: Discussionsupporting
confidence: 69%
“…This study revealed that men who were exposed to the mass media had a lower likelihood to want more children than men without media exposure. This was also observed by Gupta et al (2003), Ajaero et al (2016).…”
Section: Discussionsupporting
confidence: 69%
“…This suggests that poorer women Table 5 Decomposition of use of facility-based childbirth services gaps (Continued) have characteristics that prevent them from receiving family planning messages. Socio-demographic characteristics such as religion, residence, and marital status negatively influence the exposure to family planning information, which has also been observed in other studies [11]. It can, therefore, be said that family planning information via mass media has not been well targeted to the poor population group, and does not address their peculiarities.…”
Section: Discussionmentioning
confidence: 75%
“…This applies to the use of reproductive health care services as well. While several studies have shown that better-off women have easier access to reproductive health care [5,[7][8][9], other studies have demonstrated that socio-demographic factors such as marital status, education, occupation, residence typology, attitude of health workers, and distance to health facility also contribute to the inequality in the use reproductive health care among women [9][10][11][12][13][14][15][16]. In addition, it is unclear to what extent these determinants explain the use of reproductive health care and contribute to the differences between the groups [6,17].…”
Section: Introductionmentioning
confidence: 99%
“…This finding of the study calls for provision of due emphasis on the mass-media utilization to deliver important health messages related to IUCD [9,17,25,29]. Mass media outlets are accepted as a reliable sources of information than other sources because of many reasons such as; mass media messages are broadcasted for millions of audiences at once, messages can be nationally monitored, the approaches to deliver mass-media messages are often explicit and in a demonstrable fashion and the mass media messages can impact other important members of the family, in this instance, husbands, whom this study demonstrates are important in choosing or refusing IUCD use [30,31]. On the other hand, messages that are communicated by the healthcare providers working in the health centers might not be considered as reliable as mass media messages.…”
Section: Discussionmentioning
confidence: 99%